Answer:
y = -2x + 3
Step-by-step explanation:
<u>Step 1: Find out what each part of slope intercept form is</u>
Slope Intercept Form: y = mx + b
<em>m is the slope</em>
<em>b is the y-intercept</em>
<u>Step 2: Plug in the information into the formula</u>
m/slope = -2
b/y-int = 3
<em>y = -2x + 3</em>
<em />
Answer: y = -2x + 3
Find the slope
m= -5-6 / -8-(-2)
m= -11/-6
m=11/6
Use slope and point to create equation
y-6= 11/6(x-(-2))
y-6=11/6x+22/6
y=11/6x+58/6
y=11/6x+29/3
Change to standard form
Standard form: ax + by = c
-11/6x+y=29/3
Answer:
C^-3+d^5/f^3+g^-7
Step-by-step explanation:
The answer is as seen above
Answer:
2 pencils
Step-by-step explanation:
3 - 1 = 2